2021
DOI: 10.3390/ma14175117
|View full text |Cite
|
Sign up to set email alerts
|

SHS-Derived Powders by Reactions’ Coupling as Primary Products for Subsequent Consolidation

Abstract: The capability of self-propagating high-temperature synthesis (SHS) to produce powders that are characterized by a high sintering ability, owing to high heating and cooling rates inherent to the exothermic reaction, is of a special interest for the industry. In particular, SHS-derived powders comprise a significant defect concentration in order to effectively enhance the mass transfer processes during the sintering, which allows for the successful consolidation of difficult-to-sinter materials at relatively lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…CS or self-propagating high-temperature synthesis (SHS) is an easy and inexpensive technique with tunable thermal settings for the fabrication of Ni-W (1:1 molar or 24:76 mass ratio) composite powder from a NiO-WO 3 -Mg-C powder mixture [ 9 ]. In previous studies, SHS was shown to deliver powders of Mo-Cu and W-Cu in the nano-to-submicron size range using a similar pathway [ 10 , 11 , 12 ]. It was earlier reported [ 13 ] that the incorporation of W into Ni matrix results in grain refinement at micro and nano levels promoted properties such as hardness and wear; however, a higher amount of W induced a decrease in oxidation stability of the sintered materials.…”
Section: Introductionmentioning
confidence: 99%
“…CS or self-propagating high-temperature synthesis (SHS) is an easy and inexpensive technique with tunable thermal settings for the fabrication of Ni-W (1:1 molar or 24:76 mass ratio) composite powder from a NiO-WO 3 -Mg-C powder mixture [ 9 ]. In previous studies, SHS was shown to deliver powders of Mo-Cu and W-Cu in the nano-to-submicron size range using a similar pathway [ 10 , 11 , 12 ]. It was earlier reported [ 13 ] that the incorporation of W into Ni matrix results in grain refinement at micro and nano levels promoted properties such as hardness and wear; however, a higher amount of W induced a decrease in oxidation stability of the sintered materials.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the development of cost-effective techniques of production of homogenous and fine-grained composite materials, as well as the optimization of their preparation conditions are of current relevance. In recent years, a number of researchers [21][22][23][24][25][26][27] have offered a self-propagating high-temperature synthesis (SHS) method via a thermo-kinetic coupling approach by using an Mg + C combined reducer for producing metal-composite materials. Its essence consists in the coupling of a low exothermic reduction reaction (e.g., Ag 2 WO 4 + C) with a high caloric one (Ag 2 WO 4 + Mg), with a possible change of reaction pathway.…”
Section: Introductionmentioning
confidence: 99%
“…The literature pays great attention to the method of combustion of organometallic precursors for the synthesis of different dispersed materials. It has resulted in dozens of published reviews [1][2][3][4][5] presenting the economy and flexibility of this approach, since varying the conditions makes it possible to synthesize metals and their alloys, simple and complex oxides, supported catalysts, etc.…”
Section: Introductionmentioning
confidence: 99%